Managing physical illness through spiritual prescriptions in the “Epistle for the Sick” from Risale-i Nur - Fatah Yasin, Raudlotul Firdaus; Ismail, Masthurhah (Ankara Uluslararası Bilimsel Araştırmalar Derneği, 2025)
Risale-i Nur, or the Treaties of Light, is Bediuzzaman Said Nursi's greatest opus (1877-1960). In addition to religion and lifestyle concerns, Nursi has outlined extensively in Kitab Lama'at the vital part of human beings, which is a physical ailment with spiritual medicines. It was referred to as the Epistle to the Sick. It is produced as spiritual healing prescriptions that comprise the Twenty-Five Flashes. Nursi demonstrates the concept of health and illness through different dimensions that are viewed in the light of the Quran that the notion of illness is not something to be feared, but it brings goodness which contains many benefits, advantages and instances of wisdom. In light of the aforementioned statement, this article examines the message of the Epistle to the Sick as articulated in Risale-i Nur regarding the spiritual management of physical illness. The paper is divided into four sections. In the context of the Islamic worldview, the first section defines the spiritual aspect of human beings, which comprises the heart and intellect. It also emphasises the interdependence between the interconnected a'ql, fu'ad, and qalb. The second section examines the relationship between physical disease and spiritual demotivation in the post-COVID-19 period via global mental health concerns. In the meanwhile, the third section describes the cure of physical illness by spiritual prescription, based on Said Nursi's book Risale-i Nur. The study concludes with curricular recommendations for IIUM students, particularly those enrolled in the Kulliyyah of AbdulHamid Abu Sulayman, in order for them to become complete Muslims and active agents in propagating the wisdom of Risale-i Nur among the community